2019
DOI: 10.1109/mcom.2018.1700957
|View full text |Cite
|
Sign up to set email alerts
|

RRC State Handling for 5G

Abstract: The author of this thesis had the main responsibility in formulating the idea, deriving the results, and writing of this article. Publication II: "One-Shot Games for Spectrum Sharing among Co-Located Radio Access Networks" The author of this thesis had the main responsibility in formulating the idea, deriving the results, and writing of this article. Publication III: "Coordination protocol for inter-operator spectrum sharing in co-primary 5G small cell networks"

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The process of HO in mm-wave communications requires that the UEs makes intra-frequency or inter-frequency measurements depending on its carrier frequency and that of the BS. These measurements increases as the number of mmwave BSs increases, thereby resulting in increased power consumption for the UEs [190]. This power consumption can be minimized by reducing the measurement gaps and ensuring that the UEs take measurements within the DRX cycle.…”
Section: H Device Power Consumptionmentioning
confidence: 99%
“…The process of HO in mm-wave communications requires that the UEs makes intra-frequency or inter-frequency measurements depending on its carrier frequency and that of the BS. These measurements increases as the number of mmwave BSs increases, thereby resulting in increased power consumption for the UEs [190]. This power consumption can be minimized by reducing the measurement gaps and ensuring that the UEs take measurements within the DRX cycle.…”
Section: H Device Power Consumptionmentioning
confidence: 99%
“…In order to meet the requirements of mMTC service for low power consumption and large connection, a new RRC state (RRC connected inactive) has been proposed in 5G systems. The high-level characteristics of RRC Inactive are similar to LTE's Light Connected [9]. This new state enables the UE to maintain a connection to the core network at all times and save the UE context so that it can quickly return to RRC Connected state.…”
Section: Overview Of Rrc Protocolmentioning
confidence: 99%
“…The state machine design for the 5G radio access network (RAN) contains numerous divergent and partially contradictory 5G use cases. For this reason, the mobility framework consisting of the state machine design is one of the important issues of the control plane [22]. The RRC layer processes the control plane signals between the UE and RAN on the radio interface and controls the UE's transition mobility to the cells.…”
Section: Rrc Statesmentioning
confidence: 99%
“…In performance analysis for small packet transmission in [22], it has been observed that the RRC inactive state has a superiority over 71%, 88%, and 79%, respectively, in terms of overhead, delay, and power consumption signals compared to LTE Idle state. In the study on 5G networks containing machine-type communication in [26], it appears that adopt- ing an optimal configuration of the RC Inactive state saves more than 200% latency reduction compared to the RRC Idle state and approximately 40% UE power savings compared to RRC Connected.…”
Section: Rrc Inactive Statementioning
confidence: 99%